Fasting sugar, blood pressure and uric acid are factors related to positive Kidney disease and an impaired GFR - Al-Rumaidh, Shaymaa Z.; abdulhasn, Ahmed s.; Al-Muswie, Rana T.; Ali, Baida R. (University of Thi-Qar Journal of Science, 2022)
The purpose of this study is to determine the association between fasting sugar level, urea, creatinine, uric acid, blood pressure, and glomerular filtration rate (GFR) in renal disease patients.The current study found that men patients had lower blood sugar, fasting blood glucose, and serum creatinine levels than women patients. however, there was no significant difference between groups of blood urea, uric acid, Glumoular filter, and blood pressure. Also, there is no significant difference in patients based on age in the current study, and there is a very strong positive link between random glucose level and fasting glucose level.